KOLABORASI GURU PENDIDIKAN AGAMA ISLAM DAN GURU BIMBINGAN KONSELING DALAM MEMBENTUK KARAKTER SOSIAL SISWA DI SMP 3 PEMULUTAN - Donna Takrim; Sri Juwita; Saipul Annur; Afriantoni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the collaboration between Islamic Education teachers and Guidance and Counseling teachers in shaping students’ social character at SMP 3 Pemulutan. This research employed a qualitative descriptive approach, with research subjects consisting of Islamic Education teachers, Guidance and Counseling teachers, and students. Data were collected through observation, interviews, and documentation, while data analysis used an interactive model including data reduction, data display, and conclusion drawing, with validity ensured through triangulation. The results indicate that the collaboration is implemented through joint planning of character-building programs, the integration of learning with counseling services, and habituation as well as extracurricular activities based on social and religious values. Islamic Education teachers play a role in instilling moral and spiritual values and providing role models, while Guidance and Counseling teachers provide psychological support and develop students’ social skills. This collaboration effectively shapes students’ social character, reflected in honesty, responsibility, discipline, cooperation, and social awareness, although obstacles such as limited coordination time, differences in perspectives, and limited institutional support remain, thus requiring stronger synergy through communication, shared understanding, and school policy support to ensure optimal and sustainable collaboration.